Development of a Multi-Criteria Decision-Making Framework for Sustainable Road Transport Systems: Integrating Stakeholder-Cost-Environment-Energy Lifecycle Impacts - Hasan, Umair (Curtin University, 2019)
An MCDM framework is developed, unifying quantitative (empirical models) and qualitative (stakeholder) data for sustainability assessment of road transport systems. Highway case study data from Abu Dhabi is used to test the framework for 2015-2045 service life. Results showed that an autonomous vehicle-based bus rapid transit service in conjunction with recycled materials (warm-mix RAP, construction waste and slag) for roadworks reduced lifecycle cost (51%), energy (56%) and pollutant (55% CO2eq., 50% NOx, 24% PM) burdens.